2008
DOI: 10.1111/j.1745-6584.2008.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Simulations of Contrasting Redox Environments at an LNAPL Site

Abstract: A two-dimensional multicomponent reactive transport modeling approach was used to simulate contaminant transport and the evolution of redox processes at a large-scale kerosene-contaminated site near Berlin, Germany. In contrast to previous site-scale modeling studies that focused either on one or two contaminants or on steadystate redox conditions, multiple contaminants and electron acceptors, including mineral phase Iron (III), were considered with an evolving redox zonation. Inhibition terms were used to swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Instability of TPH aer sampling was suspected because the site is known for high microbial activity and distinct redox zonation. 18,19 However, the samples stored for seven days at +5 C did not show any TPH deterioration (ESI Fig. S4 †).…”
Section: Total Petrol Hydrocarbons (Tphs)mentioning
confidence: 98%
“…Instability of TPH aer sampling was suspected because the site is known for high microbial activity and distinct redox zonation. 18,19 However, the samples stored for seven days at +5 C did not show any TPH deterioration (ESI Fig. S4 †).…”
Section: Total Petrol Hydrocarbons (Tphs)mentioning
confidence: 98%
“…10 Other instruments such as the U. N. Body of Principles for the Protection of All Persons Under Any Form of Detention or Imprisonment, 11 U.N. Standard Minimum Rules for the Treatment of Prisoners, 12 the Convention Against Torture and Other Cruel, Inhumane, or Degrading Treatment or Punishment, 13 and U. S. military internment and interrogation policies, 14 collectively contain mandatory and voluntary standards barring U. S. armed forces from practicing torture or degrading treatments of all persons. 15 Even though the United States is a signatory government to these international conventions, the Bush Administration claims they have found various "loopholes" that have allowed for a broad interpretation of the laws. These loopholes have also contributed to the "dual loyalty" conflict among the military medical personnel.…”
Section: Dual Loyalty Conflictmentioning
confidence: 99%
“…"Pentagon officials offer many reasons for these abuses including poor training, understaffing, overcrowding of detainees and military personnel, anti-Islamic prejudice, racism, pressure to procure intelligence, a few criminally-inclined guards, the stress of war and uncertain lengths of deployment." 37 These abuses should be abhorrent to anyone.…”
Section: Ethical Analysismentioning
confidence: 99%
“…RTMs have shown that hydrocarbons in groundwater can trigger geochemical and biological reactions. Previous RTM studies have simulated the migration of PHC plumes in groundwater by combining the effects of advection, mechanical dispersion, and molecular diffusion (Cavelan et al., 2022; Picone, 2012), equilibrium and kinetic dissolution of PHC compounds (Lekmine et al., 2014; Molson & Eng, 2011), aerobic and anaerobic PHC biodegradation (Colombani et al., 2009; Miles et al., 2008; Ng et al., 2015; Prommer et al., 2002; Schreiber et al., 2004; Vencelides et al., 2007), dissolution and precipitation of carbonate minerals (Maurer & Rittmann, 2004; Spence et al., 2005), sorption of dissolved PHC to organic matter in sediments (Gharedaghloo & Price, 2021; Valsala & Govindarajan, 2018), and (de)sorption of mobilized ions (Cozzarelli et al., 2016; Miles et al., 2008; Ziegler et al., 2017).…”
Section: Introductionmentioning
confidence: 99%